La mujer y el mar en Cataluña - Eliseu Carbonell (Revue d'ethnoécologie)
In Catalonia, as in many European countries and throughout the world, women have historically played a very important role in the coastal communities, dealing specifically with tasks such as the commercialization of fish, the fish canning industry, the repair and manufacture of fishing nets, and the management of domestic groups. However, during the last third of the twentieth century, a capitalization of fishing activity took place in Catalonia and the functions traditionally carried out by women were progressively replaced by other means of mechanized work. At this point, women disappeared from the public sphere of artisanal fishing. In the collective imagination only remains the representation of the role of women in traditional coastal society through literature, art and folklore. These representations convey the image of a woman who faces her fate, often tragically, passively; A woman who waits with an attentive and anguished look towards the sea, where his man should return. Faced with this tragic and impressive image, it contrasts the image of the woman who acts, who works, who manages her opportunities, as can observe through old photographs and ethnographic accounts. This paper proposes a review of the images of women and the sea that can be found in Catalonia, both through ethnographic research and the images that have come to us through photography, art and literature. As stated in 2011 by Maria Damanaki, the European Commissioner for Maritime Affairs and Fisheries, equality between men and women in the maritime sector is still far from being a reality. This can also be observed in the cultural representation of women and sea. This is, at least, the case of Catalonia exposed in this article.